Inclusión de educandos con deficiencia intelectual en escuela públicas primarias de Carmen de La Legua y Reynoso - Callao - Api Castillo, Aldo Alfredo (2010)
There has been an investigation about the inclusive of primary schools from the state, through a design of simple descriptive investigation, we count with a sample of an available type, conformed 6 E I and a total of 19 students with intellectual handicap that involves the total of the population of kinds with intellectual handicap, also the ones from the district of Carmen de la Legua y Reynoso. An observation card has been applied to describe the characteristics of the inclusive process of these students in two stages, the first one corresponds to collect information about the inclusive education in the level of institutional planification; in the second one we observed this inclusiveness up to the level of the classroom indeed. This investigation let us analyze the process of inclusive education of this population, is advanced and in a consolidation process, especially in its socio-educative process, through a E. I. and classroom level.